Headspace versus direct injection for the quantitation of methanol, ethyl acetate, and fusel oils in distilled spirits by gas chromatography – Flame ionization detection - Janel E. Owens; Luis E. Lowe (MethodsX, 2023)
Distilled spirits can be very complex in their sensory or organoleptic compounds. Of significant interest is determination of the concentration of methanol, ethyl acetate, and fusel oils, which include n-propanol, isobutanol, n-butanol, active amyl (2-methyl-1-butanol) and isoamyl (3-methyl-1-butanol) alcohols. Here, we describe a validated method for the analysis of these analytes using a headspace (HS) sampling unit coupled with a gas chromatograph fitted with a flame ionization detector (GC/FID) for profiling these analytes in distilled spirits (n = 26) obtained from local retailers. HS results were compared to the direct injection (DI) GC/FID protocol made available by the US Alcohol and Tobacco Tax and Trade Bureau (TTB), method SSD:TM:200 via correlation and Bland-Altman difference plots to demonstrate that HS-GC/FID is a valid alternative to the direct injection protocols described elsewhere. • A method for the analysis of methanol, ethyl acetate, and fusel oils via headspace sampling coupled to a gas chromatograph fitted with a flame ionization detector (HS-GC/FID) is described. • Samples required no pre-treatment beyond diluting 1 mL of distilled spirit in 4 mL water containing table salt, which resulted in a method with minimal inlet or column maintenance, little sample prepration, and a rapid run time with retention times under 7 min. • Validation by comparing to established protocols using direct injection made available by the US Federal Tax and Trade Bureau (TTB).